KONSUMSI KUNYIT ASAM MENGURANGI NYERI HAID PADA MAHASISWI FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Muflihah, Ima Syamrotul; Riani, Evicenna N.; Margiana, Wulan (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Pain during menstruation causes discomfort in daily physical activity. This complaint is associated with recurrent disruption in school or experience complaints until it is unable to carry out activities. Many things are done to reduce the pain of primary dysmenorrhoea, for example the use of warm compresses, taking analgesic drugs, regular exercise, acupuncture, and taking herbal medicines that have been believed to be useful (Smith, 2003). Based on preliminary studies conducted at the UMP FIKES Dormitory of 15 teenage girls who experienced primary menstrual pain as many as 12 people (80%), 3 people (20%) among them did not experience menstrual pain. Of the 12 people who experience menstrual pain there are 5 people consuming sour turmeric, 2 people consuming warm ginger, 2 people warm compresses, 1 person taking analgesic medicine, 2 people relaxing. Research Objectives: To determine the difference in menstrual pain before and after consumption of sour turmeric. The type of research used in this quantitative study is a quasi experiment with a pre-post one group design design. The results of this study indicate that female teenagers who consume acidic turmeric are less than 3x having a severe menstrual pain level of 100% and girls who consume turmeric more than 3 times the acid has a severe menstrual pain of 26%. So that there are differences in the level of menstrual pain before and after consuming sour turmeric. Keywords: Consumption, Turmeric Acid. Look for Menstruation